The Relationship Between The Frequency Of Fast Food Consumption And The Incidence Of Obesity In Class X Students Of SMA Negeri 4 Jayapura - Nova Falentian Rumaropen; Ervina Eka Puteri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Obesity is a pathological condition caused by excessive fat accumulation in the body. The frequency of fast food refers to how often Siwi students consume types of fast food in a certain period of time. The impact of obesity on female students includes heart disease, type 2 diabetes, respiratory disorders, metabolic disorders, liver and kidney diseases. In 2024, the prevalence of obesity in Papua will be 294 adolescents aged 15-17 years. The purpose of this study is to determine the relationship between the frequency of fast food consumption and the incidence of obesity in class X students of SMA Negeri 4 Jayapura.This research study is quantitative analytical with a cross sectional design. The population in this study of all students in class X of SMA Negeri 4 Jayapura amounted to 578 students. The sample in this study is 236 samples. The sampling technique is simple random sampling. Data was obtained through FFQ questionnaires, height and weight measurements. Data analysis used the chi-square test with a significance limit (p) = 0.05.The results showed that 155 respondents often consumed fast food and 81 respondents (34.3%) did not eat often. Adolescents who were obese were 42 respondents (17.8%) and 194 respondents were not obese (82.2%). A total of 155 respondents (65.7%) who often consumed fast food were obese, 42 respondents (100.0%) and 115 respondents (58.7%) were not obese, while 81 respondents (34.3%) did not experience obesity as many as 81 respondents (41.8%), there was a significant relationship between the frequency of fast food consumption and the incidence of obesity p-value = 0.000 < 0.05 in class X female students.